Teaching Religious Moderation through Islamic Education: The Pedagogical Model of Islamic Education at An-Najah Islamic Boarding School - Zainuddin Zainuddin; Fuad M. Rizky Rambe; Rita Sari; Basri Basri; Mulyadi Mulyadi (TA'DIBAN, 2025)
This study examines the recontextualization of religious moderation in Islamic education through a field study at the An-Najah Islamic Boarding School. The research background stems from the need to present the values of wasatiyyah (moderation) in an applicable manner within the Islamic education system, which has tended to remain conceptual. The purpose of this study is to analyse the integration of religious moderation values into the curriculum, extracurricular activities, teacher role models, and institutional culture at the Islamic boarding school. Using a qualitative approach through field observations and in-depth interviews with three asatidz (teacher educators) (two males and one female), this study found that the values of moderation are internalised through dialogic learning, egalitarian interactions, and moral modelling. Teachers serve as models of empathetic, just, and tolerant behaviour, while Islamic boarding school activities reflect the social practice of the Islamic value of rahmatan lil-'alamin (blessing for the universe). The results confirm that Islamic boarding schools function as effective social laboratories in shaping moderate Muslim character through role models, not indoctrination. This study recommends the development of a model of integration of religious moderation based on social practice in other Islamic educational institutions to strengthen inclusive and humanistic Islamic learning in Indonesia.